Milagu Related Siddha Formulations Indicated for Various Ailments - A Literature Review (International Journal of Ayurveda and Pharma Research, 2022)
Siddha system of medicine is one of the traditional systems of medicine indigenous to south India. It is a treasure house of secret science, embodying the results of the researches done by the ancient Siddhars. In Siddha system of medicine 32 types of internal and 32 types of external medicines are used for management of diseases, which includes herbs, minerals, metallic salts and animal products. One among the herb is Milagu (piper nigrum) which is a perennial woody plant cultivated mainly for its fruits. It contains phytochemicals such as piperine, piperidine, pyrrolidines, safrole etc and possesses antioxidant, antihistaminic and bronchodilator properties. In siddha system of medicine Milagu is used in numerous poly herbal formulations which are effective in treating various ailments. This literature review aimed to analyze and summarize some of the literatures which mention Milagu as component of medicine for the treatment of ailments. About 276 Milagu related preparations were reviewed from various Siddha literatures. From the results of this review, there were 237 internal medicine, 31 external medicine and 8 were of both types, from which Chooranam and Thailam are highest in internal and external medicine respectively. This literature review gives elaborate documentary evidence related to Milagu and its medicinal uses which will be very much useful for the Siddha community